GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 13 Dec 2019, 02:56

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If a = 1 and b = -2, then (2a^2 + b)(x + y) + (a + b)(x - y) =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Manager
Manager
avatar
Joined: 18 Feb 2015
Posts: 81
If a = 1 and b = -2, then (2a^2 + b)(x + y) + (a + b)(x - y) =  [#permalink]

Show Tags

New post 23 Jul 2016, 14:19
7
00:00
A
B
C
D
E

Difficulty:

  5% (low)

Question Stats:

91% (01:00) correct 9% (01:26) wrong based on 116 sessions

HideShow timer Statistics

If \(a = 1\) and \(b = -2\), then \((2a^2 + b)(x + y) + (a + b)(x - y) =\)

(A) 0
(B) 2x
(C) y - x
(D) x - y
(E) x + y
Manager
Manager
User avatar
Status: 2 months to go
Joined: 11 Oct 2015
Posts: 103
GMAT 1: 730 Q49 V40
GPA: 3.8
Re: If a = 1 and b = -2, then (2a^2 + b)(x + y) + (a + b)(x - y) =  [#permalink]

Show Tags

New post 23 Jul 2016, 16:12
1
\(\left( 2a^{2\; }+\; b \right)\left( x+y \right)\; +\; \left( a\; +\; b \right)\left( x\; -\; y \right)\;\)

\(=\; \left( 2-2 \right)\left( x+y \right)\; -1\left( x-y \right)\;\)

\(=\; o\left( x+y \right)\; -\; x+y\;\)

\(=\; y-x\)

\(Answer\; \mbox{C}\)

Is it really from Gmatprep? It's really strange that they didn't put the x - 3y choice.
That choice would have probably been the most common mistake on this question.
Current Student
User avatar
D
Joined: 12 Aug 2015
Posts: 2550
Schools: Boston U '20 (M)
GRE 1: Q169 V154
GMAT ToolKit User
Re: If a = 1 and b = -2, then (2a^2 + b)(x + y) + (a + b)(x - y) =  [#permalink]

Show Tags

New post 29 Jul 2016, 15:14
1
Non-Human User
User avatar
Joined: 09 Sep 2013
Posts: 13742
Re: If a = 1 and b = -2, then (2a^2 + b)(x + y) + (a + b)(x - y) =  [#permalink]

Show Tags

New post 23 Nov 2019, 10:46
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________
GMAT Club Bot
Re: If a = 1 and b = -2, then (2a^2 + b)(x + y) + (a + b)(x - y) =   [#permalink] 23 Nov 2019, 10:46
Display posts from previous: Sort by

If a = 1 and b = -2, then (2a^2 + b)(x + y) + (a + b)(x - y) =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne